MANAJEMEN TPACK (TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE) UNTUK LITERASI DIGITAL TERHADAP PENGUATAN TANGGUNG JAWAB SISWA - Efendi, Yulia; Sugiawati, Iceu; Maesaroh; Anggi Jayadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In the digital era, elementary school students possess high technical fluency (digital native) but are not balanced with ethical maturity and digital responsibility, triggering negative behaviors such as cyberbullying and the spread of false information. Previous research on TPACK has focused more on teacher competency and cognitive outcomes, without addressing the systematic management aspect for strengthening students' responsible character. This study aims to describe and analyze the implementation of TPACK (Technological Pedagogical Content Knowledge) management in improving digital literacy and strengthening student responsibility in elementary schools with different environmental contexts. The research method uses a qualitative approach with a multi-site case study at SDN Cikaret Cianjur (rural) and SDN Cibeureum Sukabumi (urban). Data were collected through in-depth interviews (informants: principal, teachers, students), participant observation, and documentation studies, then analyzed using the interactive model of Miles, Huberman, and Saldaña as well as triangulation of sources and methods. The results of the study show that systematic TPACK management through the functions of planning, organizing, implementing, and controlling has proven effective in improving students' digital literacy and strengthening digital responsibility. Cibeureum Elementary School (urban) achieved higher performance than Cikaret Elementary School. Implementation challenges include limited technology infrastructure in rural areas, low TPK competency among some teachers, and a weak data-based evaluation system. The study recommends a sustainable TPACK training program, equitable distribution of ICT resources, and the development of a data-based evaluation system